Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1678403244 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "Year 1950-2021" ] } The dataset includes 1678403244 records from 27011 constituent datasets: 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 24645 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 11 records from Gulf of Maine Razorbill Tracking (aggregated per 1-degree cell). 5 records from Nannofossil abundance of Hole 6-53A. 12 records from Nannofossil abundance of Hole 29-283A. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 5104 records from Spider Mites Collection of Jean Gutierrez. 26 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 26 records from Schulteich Heinrich-Mann-Schule. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 3 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 439 records from Implementación de la bioindicación en el Río Magdalena - 2015. 1127 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1968 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 187 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 246318 records from R. L. McGregor Herbarium Vascular Plants Collection. 13 records from Coccolith counts of multinet M32/5_MSN988. 1140 records from Phytoplankton abundance in surface water during Professor Vodyanitskiy cruise PV30_1. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 9 records from Three new species of Lecteria Osten Sacken, 1888 (Diptera: Tipulidae) from a scientific survey in Mitaraka (French Guiana). 15 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2316 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras de 2009 a 2014. 7 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2125 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 183 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 214 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 15 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 498 records from Estudio poblacional del chano norteño, Micropogonias megalops y la curvina Golfina Cynoscion othonopterus (Gilbert) (Pisces: Sciaenidae), especies endémicas del Alto Golfo de California, México. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 15851 records from University of Guam Insect Collection. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 2814 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 8 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 208 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 6 records from Revision of world species of the genus Oreiscelio Kieffer (Hymenoptera, Platygastroidea, Platygastridae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 21 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1034 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4004 records from MCP-Aves - Coleção de Aves. 74 records from Área Selva de Florencia- Cantidad de área ocupada selva_2018. 135 records from Nannofossil abundance of Hole 36-329. 34 records from Revision of the French Polycirridae (Annelida, Terebelliformia), with descriptions of eight new species. 2 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 76704 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 776 records from Bird specimens of Saitama Museum of Natural History. 276 records from orthopteracollections-nhmj-ioj. 1049 records from Vertebrados terrestres de San Juan de Camarones, Durango. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 306 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10757 records from Collections of Bioclass, school #179, Moscow. 580 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 871492880 records from EOD – eBird Observation Dataset. 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 6 records from New seriated Amathia species in Japan, with a redescription of A. acervata Lamouroux, 1824 (Bryozoa: Ctenostomata). 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from Dinoflagellate abundance of Hole 14-144. 280 records from Middlebury College Bee Collection. 7 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 13 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 263711 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 167 records from Total foraminifera counts of multinet M21/6_MSN787. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 184 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part II. 8 records from Benthic macrofauna abundance of sediment core 12930-063. 9050 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 13 records from Grupo de Macroinvertebrados de la laguna Cristalina Páramo de la Rusia-Boyacá.. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 35 records from Taxonomic revision of the Neotropical genus Ormiophasia Townsend, 1919 (Diptera: Tachinidae), with the description of eight new species. 193 records from Données naturalistes de Ingénieurs écologues GEREA. 8 records from Distribution And New Records Of Lymexylidae (Coleoptera: Lymexyloidea) In Guatemala And Mexico. 8046 records from sediment metagenome Metagenome. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1155 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 1633 records from (Figure 9) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 7-12. 18 records from Naturtag. 15086 records from Herbier Louis-Marie (QFA) - Collection de lichens. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 14 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 115 records from Swedish Malaise Trap Project (SMTP) - Vespinae. 3 records from Review of Glaphyrosoma (Orthoptera: Stenopelmatoidea: Anostostomatidae) including new species and biological information. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 1709 records from suspended particulate matter Raw sequence reads. 2 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 47 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 207 records from Megafauna abundance and biomass in surface sediment during cruise PLG95A. 5 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 50 records from (Table 1) Chemical composition of segregations and groundmass seperates of ODP Leg 135 samples. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 128 records from Pollen profile 2 from Richland Creek. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 363 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1878 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 78893 records from Inventaire de la flore de Dordogne 2017. 3572 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 7242 records from Colecção Entomológica IIA. 56 records from Colección de Zoología Universidad Icesi: Insectos. 16627 records from MZFC/Coleccion de Aves. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 42133 records from TNHC Herpetology Collection. 1292 records from (Table 4) Benthic foraminifera in middle to late Miocene sediments of DSDP Hole 90-588. 143 records from Foraminifera abundance of Hole 48-406. 310 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 1052251 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 69 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 623 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel (Plantas). 3709 records from Swiss National Cicadidae Databank. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 313 records from Benthic foraminifera abundance of Hole 82-558. 722 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 83 records from DMNS Egg Collection (Arctos). 495 records from USFWS Bee surveys - Sandbar WMA, VT 2018. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 4 records from Microplankton counts and carbon biomass at station TT007_10-CTD123. 11 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 3975 records from Study on plankton at the port of Ostend in 1965. 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 162 records from Inventario forestal de una parcela permanente de restauración en el Parque Nacional Natural Alto Fragua Indi Wasi, en la vereda La Estrella, Caquetá. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 1 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 42 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2 records from First description of the female of Clubiona milingae Barrion-Dupo, Barrion & Heong, 2013 (Araneae, Clubionidae). 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 72 records from Amphibian and Reptile species occurrence records in the Tana River Basin, Kenya. 319 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 2 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1702 records from BioGIS - Bryophytes - HUJ collections. 46316 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 457 records from (Appendix B) Dinoflagellate cysts in ODP Site 170-1039 sediments. 27019 records from The Brown University Foraminiferal Data Base (BFD). 743 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 731 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 706 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 64 records from Pilzlehrwald. 2208 records from marine sediment metagenome Raw sequence reads. 1 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 7 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 106 records from Abundance of radiolaria at station UT99-5-1. 105 records from Données naturalistes de Xavier BONNET. 16 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 329791 records from Broedvogels - Atlas of the breeding birds in Flanders 2000-2002. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 44 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 43 records from Abundance of coccosphere-units of sediment core GIK23424-3. 5 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 103 records from Foraminifera species abundances from tow TT011_5-MOC63. 7 records from New Polypheretima and Pithemera (Oligochaeta: Megascolecidae) species from the Mt. Malindang Range, Mindanao Island, Philippines. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 2 records from Hagneia kallea gen. and sp. nov. (Hemiptera: Fulgoromorpha: Ricaniidae) from North Vietnam. 1244 records from Some finds of flora and fauna in Kharkiv region. 310 records from Flore des Pyrénées. 164 records from Total foraminifera counts of multinet M6/7_MSN100. 20 records from A description of the flea species Paractenopsyllus madagascarensis n. sp. and the female sex of Paractenopsyllus raxworthyi Duchemin & Ratovonjato, 2004 (Siphonaptera, Leptopsyllidae) from Madagascar with a key to the species of Paractenopsyllus. 8855 records from Données naturalistes de Benoit MARTHA. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 121111 records from Observations occasionnelles Parc national des Pyrénées. 1 records from A contribution to the knowledge of Dermestidae (Coleoptera) from Guatemala. 4 records from A new species of Decimiana Uvarov from Brazil, with updated key to species and remarks on their geographic distribution (Mantodea: Acanthopidae, Acanthopinae). 120 records from BIRDRACE The early birds. 2 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 5 records from Orthoptera Tettigoniidae as indicators of biodiversity hotspots in the Guinean Forests of Central and West Tropical Africa. 51 records from Records of the Victorian Conservation Seedbank. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 1 records from Revision of the genus Lamprima Latreille, 1804 (Coleoptera: Lucanidae). 193 records from Relative abundances of Florisphaera profunda and Helicosphaera carteri during the sapropel S5 of sediment core MD81-LC21. 2 records from First study of the Polycladida (Rhabditophora, Platyhelminthes) from the Pacific Coast of Costa Rica. 57418 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 105 records from Microfossil abundance of Hole 18-173. 1456 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 10 records from Review of the dwarf Glossogobius lacking head pores from the Malili lakes, Sulawesi, with a discussion of the definition of the genus.. 539 records from (Table 3) Distribution of calcareous nannofossils at DSDP Site 82-563 in the North Atlantic. 2560 records from Upper Silesian Museum, Bird Observations. 142 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 14110 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 267 records from SEWBReC Springtails and allies (South East Wales). 849277 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_12-CTD147. 28934 records from Pacific Reef Assessment and Monitoring Program: Rapid Ecological Assessments of Fish Large-Area Stationary Point Count Surveys (SPC) at Coral Reef Sites across the Pacific Ocean from 2000 to 2007. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 88469 records from The Himalayan Uplands Plant database (HUP Version 1). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 131 records from Artenvielfalt auf dem Schulgelände. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 58 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1391. 329 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 360 records from University of Alberta Museum of Zoology Ornithology Collection (UAMZ). 69 records from BIRDRACE Pfeifenten. 188 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 146 records from Données de la naturaliste Laurence Beauchamp. 14 records from Collections ichtyologiques et herpétologiques (BOUM). 2 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15037 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from The giant “ penis ” of a newly described species in the subgenus Scotoconiopteryx from Peru (Neuroptera: Coniopterygidae: Coniopteryginae: Coniopteryx). 14 records from Données naturalistes de ROLLAND Blandine. 14 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 50 records from La Paya, censo rápido de la flora de Jirijiri. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 7 records from Morphological differences between Stenocionops furcatus (Olivier, 1791) and S. coelatus (A. Milne-Edwards, 1878) (Crustacea, Decapoda, Brachyura, Majoidea). 6179 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 41 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 151 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 6 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 224409 records from Ocean Salmon Program - Barkley Sound Juvenile Salmon Study from 1987 to 1994. 6 records from Coccoliths in sediment core PS1532-9. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 184 records from NMML Killer Whale Vessel, Bering Sea, 1992. 44 records from MIRC KB23 Shoreline Surveys May 2013. 57913 records from Fichier communal des ongulés. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 85 records from Morphological and anatomical investigation of New Caledonian graminoid Dendrobium (Orchidaceae) with the description of two new species. 4298 records from ColRest_Raw1. 34 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 9 records from A new species of Panaqolus (Siluriformes: Loricariidae) from the rio Madeira basin with remarkable intraspecific color variation. 15 records from Nannofossil abundance of Hole 4-25. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 13 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 5678 records from SNH Bat Casework records 1970-2007. 19 records from Universidad de San Carlos de Guatemala - Colección de Equinodermos. 5 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 1708 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 35 records from Living Cirripedia. 1284 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3753 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 4276 records from University of Nebraska State Museum Birds Collection. 2 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 26687 records from University of California Santa Barbara Invertebrate Zoology Collection. 14 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 2220 records from IRAD Cameroon insect collection. 359 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 130 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 157 records from Nannofossil abundance of Hole 94-610B. 20047 records from Vertebrados terrestres del Corredor Biológico Sierra Madre del Sur, Chiapas, México. 4820 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 12 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 3077 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 100 records from Total foraminifera counts of multinet M21/2_MSN644. 2 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 5 records from New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae). 85286 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 8 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 71398 records from Fish specimens of Kagoshima University Museum. 2 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 3807 records from UTEP Invertebrates (Arctos). 6 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 1299 records from Fish occurrence in Kuban River basin. 4 records from Revision of the Traumatomutilla gemella species-group (Hymenoptera, Mutillidae) with the description of its hitherto unknown males. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 4 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 14812 records from AMNH Bird Collection. 2756 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 4 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 12 records from Happywhale - Indian humpback dolphin in Indian Ocean. 14141 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 974678 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 43 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 412467 records from DATAVES. 107 records from Projet Diable de mer - AILERONS. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 14 records from (Table S2) Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 649 records from Beetles from nature reserves and nearby forests in Østmarka. 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 3 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 2 records from Systematic Notes On Kiotina Klapálek And Hemacroneuria Enderlein (Plecoptera: Perlidae), With Description Of Four New Species. 41 records from Planktic foraminifera abundance of Hole 73-524. 6 records from Planktic foraminifera abundance of Hole 53-418B. 352 records from Flora vascular y no vascular: expedición Monte y Pinal - Proyecto Boyacá BIO UPTC. 14 records from Berea College, Ralph L. Thompson Herbarium. 1 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 409 records from Distribution of nanoplankton at trap WR2. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 382 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 141800 records from Fermanagh Flora. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_3-CTD37. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 15397 records from Macrophyte Lake Data. 1 records from Gastrodia madagascariensis (Gastrodieae, Orchidaceae): from an historical designation to a description of a new species from Madagascar. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 4484 records from Siliceous microfossil occurrence, Site 177-1091. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 70 records from Colección Herpetológica-Museo de Historia Natural Unillanos. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 596 records from Range table from benthic foraminifers in ODP Hole 149-900A. 3 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 28 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 100 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 445 records from Estudio ecológico-florístico de los enclaves de vegetación xerofítica inmersos en una selva baja caducifolia en el Istmo de Tehuantepec, Oaxaca. 79 records from Diatom abundance of Hole 95-613. 2591 records from UCLA Donald R. Dickey Bird and Mammal Collection. 258 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 63 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 8 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 2 records from Molecular phylogenetics, PCA, and MFA recover a new species of Cyrtodactylus (Squamata: Gekkonidae) from an isolated sandstone massif in northwestern Cambodia. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 9 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 1052 records from University of Vermont, Pringle Herbarium, Algae Collection. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 234 records from (Table AT9) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134B. 44 records from Description of lithologic section units of IODP Hole 325-M0041A. 14 records from Revision of the euryglossiform species of the Afrotropical bee genus Scrapter Lepeletier & Serville, 1828 (Hymenoptera: Apoidea: Colletidae). 59 records from Range table from benthic foraminifera in ODP Hole 199-1220A. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 4510 records from Carabidae of the Carpathians. 1 records from The Phalacridae (Coleoptera, Cucujoidea) of Canada: new records, distribution, and bionomics with a particular focus on the Atlantic Canadian fauna. 1808 records from 1848-1982 Lundy Field Society The Marine Fauna of Lundy. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2658851 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 15632 records from Canadian Lakes Loon Survey. 7 records from Two New Species of Composetia (Annelida: Nereididae) from Small Estuaries in the Ryukyu Islands, Southern Japan, with a List of All Species Currently Belonging to Composetia. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 401 records from Alan Wormington Collection. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 642 records from Protistan plankton diversity along salt gradient. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 3240 records from Polish gene bank – passport data of plants accessions which are important in human life. 23 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1481 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 4 records from The genus Thoradonta in Thailand (Orthoptera: Tetrigidae: Scelimeninae) with description of two new species. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 2 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 3 records from Review of the enigmatic genus Boalda with transfer of pulcherrima Köhler from Nephelistis and description of two new species (Lepidoptera: Noctuidae). 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 673 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 15198 records from (Appendix 4) Distribution of benthic foraminifers, living, dead, and total assemblage counts, and faunal diversity in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 276 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 9 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 256 records from Herpetofauna asociada a ecosistemas de Buenaventura, Valle del Cauca. EPA-IIAP 2019. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 2465 records from Elaboration de table de tarif de cubage multispécifique (I). 8239 records from Cowan Tetrapod Collection - Mammals. 11 records from High diversity and endemism in the genus Cautires Waterhouse, 1879 (Coleoptera: Lycidae) from the Malay mountain forests, with the descriptions of fourteen new species. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 36 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 184 records from Bark and Ambrosia Beetles of Vermont from Thomas H. Atkinson. 911 records from Phytoplankton abundance in surface water in May 1996, Pisco, Peru. 825 records from Pollen profile ADR309. 7 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 16 records from Insect Collections of Okomu National Park- Nigeria. 267446 records from ARABEL - Arachnologia Belgica. 25 records from Planktic foraminifera abundance of Hole 51-417B. 64 records from Carrion beetles (Coleoptera, Silphidae) of Volga-Kama Nature Reserve. 172 records from Nezara viridula records held by the Royal Horticultural Society. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1677 records from Structures and Nutrition Requirements of Macrozoobenthic Communities in the area of the Lomonossov Ridge, 1995-1998. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 728 records from South American Antarctic Marine Biodiversity Literature. 7 records from Inventario de Murciélagos en la Finca la Reserva, El Perico, Yopal, Casanare. 14387 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 472 records from Blue Mountains Swamp Archaea. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 2 records from Happywhale - in South Atlantic Ocean. 286 records from California State University, Long Beach Birds. 1479 records from Epiphytic mosses from the northwest Iberian quadrant (Spain). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 118 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 29689 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 18 records from Colecta de plantas pertenecientes a la familia Cactaceae, enmarcadas en el proyecto: Dilucidación de la sistemática de los géneros de la familia Cactaceae. 2818 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2994 records from Distribution of planktic foraminifera of sediment core M35027-1. 20826 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from A new Dondice Marcus Er. 1958 (Gastropoda: Nudibranchia) from the Mediterranean Sea reveals interesting insights into the phylogenetic history of a group of Facelinidae taxa. 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 2 records from Molecular circumscription of new species of Gyrocotyle Diesing, 1850 (Cestoda) from deep-sea chimaeriform holocephalans in the North Atlantic. 102 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 309 records from Colección de chinches (Insecta: Hemiptera) del Centro de Colecciones Biológicas de la Universidad del Magdalena. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 23829 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 2 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 612 records from Deep-sea meiobenthos at Calvi (Corsica) sampled in September 1982. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 73531 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 14980 records from Données Entomologiques A. HORELLOU 1988-2018. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Тaxonomic position of Orthochirus olivaceus (Karsch, 1881), the type species of the genus Orthochirus Karsch, 1892 (Scorpiones: Buthidae). 321 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1881 records from Données opportunistes amphibiens-reptiles du Nord et du Pas-de-Calais. 1481 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 12 records from Planktic foraminifera abundance of Hole 6-47. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 2 records from A new diurnal gecko in the genus Gonatodes (Squamata: Sphaerodactylidae) from the foothills of the Serranía de San Lucas, Norosí-Colombia. 817 records from DOW-2. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 119 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 7 records from Revision of the Agrilus gratiosus species-group (Coleoptera, Buprestidae, Agrilinae). 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 245 records from Planktic foraminifera counts of sediment core V14-77. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 126 records from Bryological collection of Yugra State University. 4 records from Bemerkenswerte Faltenwespen aus der äthiopischen Region. Teil 14 (Hymenoptera, Vespidae, Eumeninae). 131 records from (Table 1) Middle Eocene silicoflagellates from DSDP Hole 95-612. 1110 records from FFH-Gebiet "Calwer Heckengäu". 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 858 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 14 records from Revision of the subgenus Stigmatophorella of Chalcophorella (Coleoptera: Buprestidae: Chrysochroinae). 81532 records from Bob Merritt Coleoptera Dataset. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 51 records from Nannofossil abundance of Hole 20-199. 565 records from Counts of the living benthic foraminifera assemblage in surface sediments of the North Atlantic. 232 records from Planktic foraminifera abundance of Hole 21-207. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 160 records from Données espèces - Expertise IPE 37. 431 records from Nannofossil abundance of Hole 74-528A. 10763 records from WOLL AVH data. 12540 records from Recensement des espèces en vue de l'élaboration du répertoire des forêts sacrées, forêts galeries, savanes et autres formation floristique du Bénin.. 2 records from A new species of leaf-toed gecko (Phyllodactylidae, Phyllodactylus) from Maria Cleofas Island, Nayarit, Mexico. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 154 records from Shannon Index and species richness for arthropods. 31 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 156 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 67 records from Monitoreo de la ocupación del Oso de antejoso (Tremarctos ornatus) en el Parque Nacional Natural Las Hermosas Gloria Castaño de Valencia para 2017 y 2018. 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 2184 records from Phenological Center - Plants (Laplandskiy). 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 572 records from Benthic foraminifera abundance of Hole 84-567A. 2497 records from Données des collections d'algues du MNHN. 2326 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 75 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 1552 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 16745 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 154 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 75 records from UWIZM Cnidarians. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 75 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 165738 records from Tasmanian Museum and Art Gallery provider for OZCAM. 936 records from TTRS Mammals. 5 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 1547 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 45 records from Brown bear monitoring data from Deosai National Park. 469 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 92645 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 29 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 312 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 28 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 89 records from Faunal assemblage of sediment core TR149-32. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 581 records from La familia Asclepiadaceae en México. 2 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 370 records from Otter survey of Ireland 2004 & 2005. 1055 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1292 records from Happywhale - Gray Whale in North Pacific Ocean. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 14 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 295 records from Données de VINCENT Alexis (SAPROX). 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 117714 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 494 records from (Table 6) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 2848 records from Tableaux de prélèvements communaux. Réseau Ongulés sauvages ONCFS-FNC-FDC. 1 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 11873 records from Midden-Limburg Fish Ponds Survey. 56137 records from Herbarium (ICEL). 53975 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 4 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 243 records from Cactophilic Drosophila and Opuntia. 2 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 22530 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 17 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2 records from Umbellula pomona sp. nov., a new sea pen from Mar del Plata Submarine Canyon (Cnidaria: Octocorallia: Pennatulacea). 836 records from SEFSC GoMex Oceanic 1993 (W). 44531 records from WCPS Bird Survey Project. 1 records from Planktic foraminifera abundance of Hole 4-26. 106 records from Sylter Meerstrandläufer. 717 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 3 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 37872 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 11693 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 4 records from Range table from planktonic foraminifers in ODP Hole 151-912C. 9156 records from NEON Biorepository Carabid Collection (DNA Extracts). 225 records from Tillegg Røtinga i Os. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 17 records from Données naturalistes de Franck MERLIER. 192 records from Total foraminifera counts of multinet M10/2_MSN218. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 1338 records from (Table 9) Distribution of planktonic foraminifers in ODP Site 112-687. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 9204 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 9974 records from Inventario de Hymenóptera; parasítica en México. 3869 records from UAM Herbarium (ALA), Algae Collection (Arctos). 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8428 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from A new genus of mongoliulid millipedes from the Far East of Russia, with a list of species in the family (Diplopoda, Julida, Mongoliulidae). 1785 records from 3Soil16S. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 2579 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 6 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 2 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 193 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 1 records from Multiple lines of evidence reveal a new species of Krait (Squamata, Elapidae, Bungarus) from Southwestern China and Northern Myanmar. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 1 records from Synonymies, new records, and new species in Cerambycinae (Coleoptera Cerambycidae). 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 628 records from SWFSC Marine Mammal Survey, Vaquita 1997, Cruise 1608. 193 records from Planktic foraminifera counts of sediment core RC11-134. 27155 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 70 records from Birds Specimens of Akita Prefectural Museum. 7 records from Urochordeumatidae Silvestri, 1909, a millipede family endemic to Washington State, USA (Chordeumatida, Striariidea, Striarioidea). 2191 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Crustáceos). 102 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 136 records from Oberes Schindelbachtal. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 177831 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-78. 130845 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 34 records from Propuesta de diagnóstico, erradicación y monitoreo post-erradicación, de especies exóticas invasoras en oasis de Baja California Sur, centrándose en las dos más relevantes: rana toro Lithobates catesbeianus y manto de cristo Cryptostegia grandiflora. 2721 records from Whale catches in the Southern Ocean. 2 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 14860 records from Floristic diversity of the protected areas of Mont Kouffé and Wari Maro in the north of Benin. 1 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 134 records from Mycoblitz 2017 - IRBV et Cercle des Mycologues de Montréal. 230 records from Biometría peces Parque Nacional Natural La Paya. 61 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1933 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 417 records from Benthic foraminifera counts of sediment core GIK23351-1. 11 records from Benthic macrofauna abundance of sediment core 13077-063. 4148 records from WII Herbarium Dataset. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 24046 records from Quaid-i-Azam University Herbarium. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 1687309 records from NBIS Records to December 2016. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 22 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 3320 records from BioGIS - Mammals - SPNI. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 7603 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 1599 records from MEXU/Flora de Oaxaca. 31406 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6162 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 1841 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 2851 records from Données naturalistes d'Alain BERLY. 27418 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 12711 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 205782 records from Données de la flore d’Alsace (SBA). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 835 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 24880 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 168 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 103165 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1386052 records from Flore Franco-Belge. 16548 records from EAC - Herbário Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1519 records from Leif Richardson Vermont Bee Specimens. 7 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 3874 records from Collection Crustacea - ZMB. 53 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 1 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 18 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 6554 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 324 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 18 records from Happywhale - Sei Whale in South Pacific Ocean. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 215 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10046 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16505 records from Database for alien invasive plants occurrences in Germany. 60 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1334 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 407 records from Strathclyde badger sett surveys 1996-2000. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 4332 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 322 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 10612 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 2791 records from Inventaire des Mollusques Sphaeriidae de France. 16885 records from données aranéologiques de CORNIC Jean-François. 48 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 3345 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3460 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 1 records from A new species of Isometopus from Iran (Hemiptera: Heteroptera: Miridae: Isometopinae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 2599 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 10477 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6 records from 2. Donauinsel bei Entau. 2 records from Happywhale - False Killer Whale in South Atlantic Ocean. 39 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 284 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1139 records from Ornithologie Federsammlung - SNSD. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 90 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 46 records from Liether Park (LMS), 5a. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 370 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 13 records from Coleção de Coleoptera da Universidade de Brasília. 98 records from Warnowtal (Rostock). 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 311 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 386063 records from Compost microbe establishment and growth in agricultural soils. 13 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202122 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351460 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 181351 records from Carnet B Lorraine. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 360958 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 7 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 963 records from Collection Trichoptera - SMF. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 99 records from Planktic foraminifera abundance of Hole 27-262. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 27 records from Planktic foraminifera abundance of Hole 27-260. 128770 records from Arizona State University Hasbrouck Insect Collection. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3347 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1369 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 347 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 87901 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 36 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 28994 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 61 records from Shrews of Poland. 9 records from Nannofossil abundance of Hole 2-11. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 145 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59978 records from Données naturalistes de Monsieur François FOURNIER. 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 53824 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 39 records from Planktic foraminifera abundance of Hole 14-137. 1156 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 124 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 23138 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 10 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6433 records from Modernisation des ZNIEFF du PnrL. 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 1264 records from Grand Voyeux - Suivis scientifiques. 36 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 72142 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 21591 records from Weevil and Bark Beetle records via iRecord. 39 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 66 records from Planktic foraminifera abundance of Hole 22-212. 2 records from Nannofossil abundance of Hole 4-26A. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 33 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 60 records from Wichita State University Collection. 86 records from Données naturalistes de Pierre-Alexis RAULT. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 227 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 217 records from NZCS Upper Tapanahony Expedition 1991. 303 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 3 records from DD_cyano Targeted loci environmental. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 7 records from Happywhale - Northern Right Whale Dolphin in North Pacific Ocean. 2 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 7 records from Genus Stathmopoda Herrich-Schäffer, 1853 (Lepidoptera: Stathmopodidae) from China: Descriptions of thirteen new species. 8 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 22 records from Ahuyentamiento, rescate y reubicación de fauna en el área de influencia directa del proyecto Hidroeléctrico Mulatos II. 6652 records from Inventory of plant species through Benin (West Africa). 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 17 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 2011 records from UNCW Right Whale Aerial Surveys 2008. 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 956 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 25774 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 23 records from Happywhale - Crabeater Seal in Southern Ocean. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 33 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 316 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 18 records from Happywhale - Short-finned Pilot Whale in North Atlantic Ocean. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 4254 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 74 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 2225 records from Données naturalistes d'Anaïs MAS. 862 records from Palynological analysis of sediment core GeoB9508-5. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 9 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 7 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 21382 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 4 records from Planktic foraminifera abundance of Hole 17-166. 283 records from Flux data of NU2_trap (Table A1). 2844793 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 227 records from Bishop's University Insect Collection (BUIC). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 5346 records from Sediment metagenome. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 1563 records from Occurrences of the Insects in the Prioksko-Terrasny biosphere reserve. 21 records from Happywhale - Blue Whale in Southern Ocean. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 734 records from CNAN/Scorpiones. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 19665 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 243 records from Thistles species and abundance. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2096 records from Flora vascular acuática de la cuenca del Río Tamesí. 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 195 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 249 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 21 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 30 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 6 records from Foraminifera abundance of Hole 58-442. 644 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 18 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 109 records from Planktic foraminifera abundance of Hole 18-181. 2 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 13555 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 13 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2041 records from marine metagenome Targeted Locus (Loci). 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24471 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 36 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 10825 records from Census of species recorded during phytosociological surveys in Benin. 6237 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 1 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 9660 records from Collection Pisces SMF. 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41140 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 1 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 13434 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 284240 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 7 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 13 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 36622 records from Botanical Museum, Copenhagen, Mycology Herbarium. 5 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 10547 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 22 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 91352 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 211863 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 4 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 13 records from Type locality records of Polycystididae species in the world. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 772 records from Données naturalistes de Stéphane ORIO. 343 records from Inventario herpetofaunístico del noroeste de Hidalgo. 32256 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 244 records from WildesMoor bei Schwabstedt. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 7 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 198 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Bolbelasmus (Bolbelasmus) zagrosensis (Coleoptera: Scarabaeoidea: Bolboceratidae), a new species from Iran, along with an updated key to the western Palaearctic species of the subgenus. 108 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 150 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 1 records from Notes on the tribe Tongini, with description of a new species of the genus Orthophana from northern Vietnam (Hemiptera: Fulgoroidea: Nogodinidae). 2181 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 3647 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 106 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 29 records from Total foraminifera counts of trap L3_92_45. 43 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 3 records from Impatiens wutaishanensis (Balsaminaceae), a new species from Southeast Yunnan, China. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 107 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 2 records from Hawksbill turtle - Milman Island (aggregated per 1-degree cell). 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 69 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 31 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 3 records from Records and redescription of a mygalomorph spider genus ignored for over 100 years with a new species: the genus Atmetochilus Simon, 1887 (Araneae Nemesiidae) in Thailand. 332572 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 402 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 59951 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1719 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 230 records from Inventaire avifaune. 29814074 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Lysimachia rupestris F. H. Chen & C. M. Hu (Primulaceae): a new record for the flora of Vietnam and reconsideration of its taxonomical position. 117 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 33 records from Bohemannia auriciliella (Nepticulidae) specimen data. 13 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 74 records from Nannofossil abundance of Hole 39-359. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 217 records from Inventaire des odonates 2014. 113 records from Nannofossil abundance of Hole 49-412. 16 records from Genética de la Conservación del Oso Andino en el Parque Nacional Natural Cordillera de los Picachos y área de amortiguación. 24 records from Abundance of benthos infauna at station PS1240-1. 1716 records from Marine algal flora of Flores and Corvo Islands, Azores. 1079 records from Mediterranean seabird surveys 99/00/02. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 688 records from données arachnologiques de CARR David. 4 records from Nannofossil abundance of Hole 3-22. 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 5 records from Description of Coeliccia natgeo sp. nov. from Central Vietnam with keys to the males and females of the hayashii-group (Odonata: Zygoptera: Platycnemididae). 134 records from BIRDRACE Griffin Wood Warblers. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 91 records from Marybio Foundation marine mammal aerial sightings in Bahia San Antonio, Patagonia 2008-2010. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 8 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 25476 records from JCT AVH data. 33 records from Planktic foraminifera counts of sediment core V28-128. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 23 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 433 records from Amphibiens de Guyane. 134 records from Nannofossil abundance of Hole 7-62A. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 11 records from Nannofossil abundance of Hole 9-82. 8 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from Planktic foraminifera abundance of Hole 20-200A. 575 records from Nannofossil abundance of Hole 75-530A. 44 records from Happywhale - Fin Whale in South Atlantic Ocean. 4 records from Collection Myriapoda - SNSD. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78045 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 2 records from Notes on the subspecies of Plagionotus arcuatus (Linnaeus, 1758) with description of a new subspecies from Iran (Coleoptera: Cerambycidae). 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3445 records from Dorset SW Pilot species dataset. 68 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4 records from Herbarium Senckenbergianum (FR) - Protista. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 52527 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 4117 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 3 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 285 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 123285 records from Herbarium of Taiwan Forestry Research Institute. 23 records from Ackerrain Plönhagen. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 239 records from Malawi-Histeridae-Biodiversity-Data. 426 records from Planktic foraminifera abundance of Hole 7-64. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 20668 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 910 records from Alien plants of Salavat. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 4 records from Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species. 35 records from Inventaire et suivi de la faune écrasée. 1000 records from nsmk_mm_2019. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 16289 records from Vegetation of Rybachy Peninsula and Srendny Peninsula, Murmansk Oblast, Russia. 1667 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 982 records from Diatom assamblage in samples from sediment trap OG4. 497 records from DAR AVH data. 9 records from Happywhale - Commerson's Dolphin in South Atlantic Ocean. 170543 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 836 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1 records from New morphological information on Simulium wygodzinskyorum Coscarón & Py-Daniel, 1989 (Diptera: Simuliidae). 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 145 records from Gronau - auf der Suche nach dem Neunauge. 95 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 1120 records from Programme national de science participative sur la Biodiversité Littorale (BioLit). 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 12 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 2068 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 613 records from Implementación de la bioindicación en el Río Cauca - 2016. 104 records from BID-Malawi-Arctiidae-Biodiversity-Data. 1 records from Spiders of the mungaich group from Western Australia (Araneae: Salticidae: Euophryinae: Maratus), with one new species from Cape Arid. 2 records from pp 56 - 66, plates 1 - 4 in Monographie des Libellulidées d'Europe. 122 records from BIOTOPE_2017_12_18. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 108 records from BIRDRACE Diesmal sehen wir mehr. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 16 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1763 records from Arachnida of Costa Rica (INBio). 675 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 3132 records from Ross A. Layberry, Collection. 3 records from Contribution to the knowledge of subterranean ground beetles from eastern Wuling Mountains, China (Coleoptera: Carabidae: Trechinae). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 92 records from Microfossil abundance of Hole 50-416A. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 10 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 1822 records from Galathea II, Danish Deep Sea Expedition 1950-52. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1 records from Contribution to the knowledge of the Clytrini of the Eastern Mediterranean, the Near East and the Arabian Peninsula, with descriptions of four new species (Coleoptera: Chrysomelidae: Cryptocephalinae). 411 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 17 records from North Carolina Rehabilitated Sea Turtle Monitoring Project (aggregated per 1-degree cell). 5911 records from Colecção Entomológica do Museu de História Natural de Maputo. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 722 records from Heritage Trees of Ireland. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 613 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 372 records from Collection Polychaeta - ZSRO. 16774 records from imr_mareano_rpsledge. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 41269 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 932 records from CNAN/Araneae. 42 records from Estimated plankton abundance at station PS63/064-6. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 29 records from New apinnate Prionospio (Annelida: Spionidae) species from southeastern Brazil. 71 records from Evaluación de la diversidad biológica y las relaciones tróficas de las charcas estacionales del norte de La Guajira. 317 records from A revision of the shield-back katydid genus Neduba (Orthoptera: Tettigoniidae: Tettigoniinae: Nedubini). 372 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 1074 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 3 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 15 records from Inventaire et suivi de la Cistude d’Europe sur le site Natura 2000 ‘Zones humides de Moliets, La Prade et Moisans’ (FR7200718). 9 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 89 records from Colección de Zoología Invertebrados - Helmintología. 2 records from A new species of the “ apacheanus ” group of genus Pseudouroctonus from western Texas (Scorpiones: Vaejovidae). 89 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 79 records from Total foraminifera counts of multinet POS247/2_MSN1384. 27509 records from Fishes of INEP and NFH collections. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 46 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 54 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 75 records from Naturpark Kottenforst-Ville 19.6.09. 3 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 227 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 1 records from Happywhale - Sei Whale in Southern Ocean. 3 records from A new pygmy species of box jellyfish (Cubozoa: Chirodropida) from sub-tropical Australia. 6 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 2 records from Descriptionoftwonew speciesofDinetus Panzer, 1806 (Hymenoptera: Crabronidae Dinetinae) with key to species. 18 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 136 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 6041 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 69 records from Montana State University - Billings. 70 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 333 records from renaturierter Main (Kemmern bei Bamberg). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 479 records from Geochemistry and sedimentology on core POS200/10_28-1. 413 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 132155 records from Observations Regelink Ecology and Landscape. 3960 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 9443 records from Batsites inventory for England (1949-2011). 58483 records from Isopoda (Interim dataset). 1 records from A new epigean species of the genus Anelpistina (Insecta: Zygentoma: Nicoletiidae) from Sierra de El Abra, Taninul, Mexico. 5 records from A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan). 89 records from Microbes in drinking water and biofilms (18S rDNA amplicon study). 672 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 173037 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 177 records from Anfibios y reptiles del municipio de Cimitarra, Santander - Proyecto Santander BIO. 474 records from Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 2577 records from Algae collection, Oslo (O) UiO. 5 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 6 records from Nannofossil abundance of Hole 6-49. 29 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 5061 records from Metagenome from mudbank Area,Alappuzha Kerala India. 2 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 55 records from Planktic foraminifera abundance of Hole 16-161. 7003 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 13 records from Guinea-Bissau Herpetological Collection - IICT. 1 records from Psilotris vantasselli, a new species of goby from the tropical western Atlantic (Teleostei: Gobiidae: Gobiosomatini: Nes subgroup). 967 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 869 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 97 records from Happywhale - Minke Whale in North Atlantic Ocean. 34 records from Planktic foraminifera counts of sediment core V27-47. 20 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 1 records from On the rare Neotropical genus Ophionthus Bernhauer (Coleoptera: Staphylinidae: Staphylininae): redescription of the type species and description of a new species. 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1460 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 368 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 102 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 278 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 231 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 2 records from Bracon planitibiae sp. nov. (Hymenoptera: Braconidae), a new parasitoid of Asian longhorned beetle (Anoplophora glabripennis). 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 73340 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 77 records from Benthic foraminifera abundance of Hole 42-372. 1338 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 469132 records from Natural England Marine Monitoring surveys. 705 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 10 records from Four new species and further contributions to the Leuctridae (Plecoptera) of the Korean Peninsula. 2867 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 17 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 75 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 1 records from Amphicnemis rigiketit sp. nov. from Sarawak, with notes on Amphicnemis remiger Laidlaw, 1912 (Odonata: Zygoptera: Coenagrionidae). 1416 records from Coleoptera Collection. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 403 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1260 records from Kangawalla Bird Sightings. 432 records from Gabon 2008-09: Mayumba & Pongara, Leatherback Turtles (aggregated per 1-degree cell). 23 records from Michigan Plecoptera (Stoneflies): Distribution Patterns And An Updated Species List. 209 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 2128 records from Occurrence (present/absence) and abundance of zooplankton in Murchison Bay, Lake Victoria. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 141 records from Importancia del Parque Estatal Cerro de la Tortuga para la conservación de los mamíferos del estado de Morelos, México. 1135 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 20 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 3 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 16593 records from Florida Manatee Synoptic Aerial Survey 1991-2019. 213 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 4 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 671 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 40832 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 2 records from Meschia zoui sp. nov., first representative of the family Meschiidae from China (Hemiptera: Heteroptera: Lygaeoidea). 8 records from Genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) from Laos, with descriptions of five new species. 53961 records from Long-Term Monitoring Network Vegetation Quadrats. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 83 records from Naturpark Kottenforst-Ville 16.6.09. 5 records from Description of two females of Leptagrion Selys (Odonata: Coenagrionidae). 244 records from Planktic foraminifera abundance of Hole 15-154A. 5 records from Inventaire des sangsues - détermination des échantillons de l'enquête participative - Subvention UMS Patrinat. 78151 records from Birds ringed by Revtangen Bird Observatory 1936-2018, Southwest Norway. 231 records from Données du/de la naturaliste HAYON Bruno provenant de la base de donnée du SINP Île-de-France CETTIA. 323 records from Inventaire floristique dans le cadre le cadre de l'Aménagement de la forêt classé de l'Amou-Mono (Togo). 24 records from Bombus impatiens Cresson (Hymenoptera: Apidae, Apinae, Bombini) from the Prairies Ecozone in Canada. 40 records from Microzooplankton abundance and biomass at station TT043_21-22. 942 records from Données de la structure Agence des Espaces Verts provenant de la base de donnée du SINP Île-de-France CETTIA. 5144 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 2849 records from Inventaire et suivi Odonates. 3978 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 72215 records from Reef Life Survey - Survey Records. 8951 records from North Marine Region sea snake collection records (DEW collation), Australia (1877-2007). 147 records from Diversity and distribution of Pleioplectron Hutton cave wētā (Orthoptera: Rhaphidophoridae: Macropathinae), with the synonymy of Weta Chopard and the description of seven new species. 1 records from Données naturalistes de Benoit CARATY. 1 records from Chroesthes (Acanthaceae) in Peninsular Malaysia, including a new species from Kelantan and a new record from Terengganu. 89 records from Données du naturaliste Xavier Houard. 70366 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 6 records from Hyptidendron pulcherrimum Antar & Harley, sp. nov. (Hyptidinae, Lamiaceae), a new narrowly endemic species from Minas Gerais, Brazil. 198 records from Planktic foraminifera distribution of sediment core 75KS5. 24 records from Nannofossil abundance of Hole 26-250. 18 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 2 records from The InBIO Barcoding Initiative Database: Depressaria infernella Corley & Buchner, a new Iberian species of the Depressaria douglasella group. 8 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 3 records from Ostracoda abundance of Hole 13-134. 48 records from An overview of the Brazilian inselberg genus Ameroglossum (Linderniaceae, Lamiales), with the description of seven new species. 149 records from Données du/de la naturaliste CHAPUIS Vincent provenant de la base de donnée du SINP Île-de-France CETTIA. 55 records from Données du/de la naturaliste Marmet Nicolas provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Swedish Malaise Trap Project (SMTP) - Clusiidae. 22969 records from UPCB - Herbário do Departamento de Botânica. 2 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 9 records from A new species of Probolomyrmex from Madagascar.. 1487 records from Database of Eurasian beaver (Castor fiber L., 1758) in Natural Reserves and National Parks of Russia. 4 records from A new species of tree-hole dwelling freshwater crab of the genus Arachnothelphusa Ng, 1991 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from northern Sarawak, Malaysia, Borneo. 277 records from Phytoplankton abundance at bottle station A1/52. 1017 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 3489 records from ZFMK Coleoptera collection. 1 records from Bipolarity in sea slugs: a new species of Doridunculus (Mollusca: Nudibranchia: Onchidoridoidea) from Antarctica. 27566 records from Records of protected animals species in Ukraine. 223 records from Range table from planktonic foraminifers in ODP Hole 170-1043A. 125 records from annex3. 43160 records from Ireland's BioBlitz. 336 records from Eschlberg Thalhausen. 57 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 24 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 42 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 28512 records from Prokaryotic microbial communities structure in the headwater watchment of Dongjiang River in the south of China. 1426 records from Kartlegging av kortdistansespredning av fremmede bartrær - Helgelandskysten. 14 records from A revision of Palaearctic and Oriental Pseudolathra. V. Two new species from Cambodia and Thailand, and additional records (Coleoptera: Staphylinidae: Paederinae). 51 records from Range table from planktonic foraminifers in ODP Hole 173-1067A. 21 records from HRC SCC Aerial-Based Monitoring Surveys 2008. 441 records from British spiders in the collections of World Museum, National Museums Liverpool. 647 records from (Table 3) Calcareous nannofossil distribution on ODP Hole 117-720A. 4 records from Two new species of Flavoperla (Plecoptera: Perlidae) from Shaanxi Province of China. 8 records from RISC Non-Native Species Records for Zebra Mussel. 139 records from Nannofossil abundance of Hole 55-433. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 218340 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 5 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 7 records from A revision of the systematics and distribution of the damselfly genus Prodasineura Cowley, 1934 (Odonata: Zygoptera: Platycnemididae) in Vietnam with description of two new species. 43 records from Vogelstimmenführung durch den Tiergarten. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 2975 records from Tetrápodos de Uruguay. 50 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 4 records from Craspedotropis gretathunbergae, a new species of Cyclophoridae (Gastropoda: Caenogastropoda), discovered and described on a field course to Kuala Belalong rainforest, Brunei. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 195 records from Données de la naturaliste Giordano Charlotte provenant de la base de donnée du SINP Île-de-France CETTIA. 7994 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 3 records from Larval morphology and life history of Eutrichosoma mirabile Ashmead and description of a new species of Eutrichosoma (Hymenoptera, Chalcidoidea). 22 records from Propriété régionale du Moulin des Marais - Inventaire naturaliste 2015. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 7 records from Three new species of the genus Mimetus Hentz, 1832 (Araneae: Mimetidae) from Yunnan-Guizhou Plateau of China. 10295 records from University of Kentucky Insect Collection. 51225 records from Atlas des Orthoptères et Mantides de France métropolitaine. 23 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 64 records from Données du/de la naturaliste Bourdin Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A remarkable burrow-dwelling alpheid shrimp, new genus and new species, from the tropical eastern Pacific (Malacostraca: Decapoda: Caridea). 667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 24 records from Ostracoda abundance of Hole 48-406. 391 records from GEOECOLINK_2017_12_18. 2 records from Updates to the bee fauna of Portugal with the description of three new Iberian Andrena species (Hymenoptera: Apoidea: Anthophila). 1113 records from UTEP Herpetology Osteology (Arctos). 16 records from A survey of Agroeca Westring, 1861 from China (Araneae: Liocranidae). 135990 records from The Scottish Squirrel Database. 36 records from Planktic foraminifera counts of sediment core V26-124. 168 records from Caracterrización florística del humedal La Abuelita, Municipio de Guapi-Cauca, 2018. 36 records from Selz (Ingelheim am Rhein). 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 2 records from A new species of Notomulciber (Micromulciber) Aurivillius, 1913, from the southern Western Ghats of India (Coleoptera: Cerambycidae: Lamiinae: Homonoeini). 14 records from Collection Crustacea - KAUMM. 332 records from Anfibios y Reptiles de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 329 records from FBIP: Baboon spider distribution records from selected South African museums. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 3 records from Record of the Non-native Suckermouth armored catfish hybrid Pterygoplichthys pardalis (Castelnau, 1985) x Pterygoplichtys disjunctivus (Weber, 1991) (Siluriformes: Loricariidae) in Honduras. 1023 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 9 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 4 records from A new species of Pselaphogenius Reitter, 1910 of the fiorii species group from southern Italy (Coleoptera, Staphylinidae, Pselaphinae). 3909 records from Royal Ontario Museum Fungarium (TRTC). 3188 records from Butterfly_conservation_2017_12_18. 1 records from A new species of Dixonius (Squamata: Gekkonidae) from Vientiane Capital, Laos. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 125793 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 13 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 28624 records from Données bibliographiques et opportunistes Odonates issues du SIRF. 2736 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 502 records from Metagenome microbial communities of bottom sediments of the Kara Sea. 99 records from Düne am Ulvenberg (Darmstadt). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 101 records from HRC CRC Small Vessel-Based Monitoring Surveys October-November 2011. 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 1906 records from Swiss Psyllid (Hemiptera) Collections - Basel. 61 records from Virginia CZM Wind Energy Area Survey- Vessel Survey Sightings - November 2012 through April 2014. 12 records from Four new species of Plumachaetas Salmon (Collembola: Entomobryoidea) from Oceania with comments on the genus and a key to species. 2 records from Two new species of the genus Bolboceras Kirby, 1819 (Coleoptera: Bolboceratidae Bolboceratinae) from India with an updated identification key of the Bolboceras nigricans Westwood, 1848 species group. 15 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 1640 records from Pilotovervåking av dragehode Dracocephalum ruyschiana. 338 records from Planktic foraminifera abundance of Hole 15-148. 257 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 3528 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 172 records from Mollusca specimens of Kuroshio Biological Research Foundation. 425 records from données bibliographiques diverses (non araignées). 1518 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 22 records from New records of ant species from Yunnan, China. 22 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 95 records from Nannofossil abundance of Hole 22-217. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 1 records from First occurrence of Anacroneuria singularis Righi-Cavallaro & Lecci, 2010 (Plecoptera: Perlidae) in Rondônia, western Amazonia, Brazil. 83 records from Total foraminifera counts of multinet M21/5_MSN728. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 2 records from Description of larva of Euphaea superba Kimmins, 1936 (Odonata: Zygoptera: Euphaeidae) from China. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 85 records from Données espèces - Expertise IPE 123. 60 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 50 records from Beetles on polypores at 4 sites in Norway. 1224 records from Microbial diversity associated with copepods in the North Atlantic subtropical gyre. 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 1447 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 89 records from Amphibians and Reptiles in Selected Sites in Palawan Province, the Philippines. 1 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 682 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1554 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 157 records from BIRDRACE Rheinische Wasserrallen. 4 records from Two new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from Pakistan. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 3 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 1144 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 4579 records from Données naturalistes de David HAPPE. 5 records from A taxonomic review of the genus Dicranorhina Shuckard (Hymenoptera: Crabronidae: Crabroninae) from the Indian subcontinent with the description of three new species from Southern Western Ghats. 493 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 106 records from Total foraminifera counts from multinet M31/2_MSN890. 2535 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 273 records from Freshwater Bullhead Survey Data in Wales. 54 records from Taxonomic studies on the sac spider genus Clubiona (Araneae, Clubionidae) from Xishuangbanna Rainforest, China. 5 records from Three new species of Polana (Varpulana) (Hemiptera: Cicadellidae: Gyponini) from Brazil, with updated key to males and taxonomic notes on the female genitalia. 92 records from Planktic foraminifera abundance of Hole 9-80. 1098 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 399 records from Analysis of the macrobenthic community near Nieuwpoort (1970-1971). 456824 records from SER Species-based Surveys. 84 records from Muestreo de Oenocarpus bataua en los flancos este y oeste de la cordillera oriental Colombiana. 4 records from A new lacewing species of the Chrysoperla carnea species-group from central Asia associated with conifers (Neuroptera: Chrysopidae). 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 4 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 5 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 1139 records from Macromycetes in Portugal Update. 6 records from Five new species of Homalotylus Mayr (Hymenoptera: Encyrtidae) - from India with a key to Indian species. 100 records from orstom_macassar_corindon_1980. 3993 records from PNR_Alpilles_2017_12_18. 1239 records from (Figure 3) Distribution chart of creatceous planktonic foraminifera of ODP Hole 122-762C. 93 records from Höltigbaum. 4 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 428 records from Swedish Malaise Trap Project (SMTP) - Auchenorrhyncha excl Delphacidae. 26 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 3920 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 159 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK17732-1. 2034 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 99 records from BIRDRACE TEAM BO-BACHTER. 56 records from Zitadelle Berlin-Spandau (7b). 1565 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 82 records from General Biodiversity Records from Ireland. 13 records from Oberservation of birds at station PS14/159 along 49° West. 459 records from Enquête Abondance Grande faune forestière de Guyane (ONCFS). 1 records from A new Pararistolochia Hutch. & Dalziel (Aristolochiaceae) from the Beanka Tsingy (western Madagascar). 1302 records from Winter colonies of Kuhl's bat (Pipistrellus kuhlii subsp. lepidus Blyth, 1845) in Ukraine, 2013-2020. 14 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD38. 3 records from New genus of the subfamily Oscinellinae from Brazil (Diptera: Chloropidae). 68 records from Sandhofen. 967 records from Relevé flore exotique isolée de La Réunion. 208 records from Inventory of Synsepalum dulcificum Daniell in south Benin. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 2 records from Heizmannia rajagopalani n. sp. (Diptera: Culicidae) in Kerala, India, a species previously misidentified as Hz. metallica (Leicester). 61976 records from marine sediment metagenome Metagenome. 66 records from Dinoflagellate cysts from sediment core PS2458-4. 3 records from Chronicle of Nature - Phenology of Arachnids of FGBU GPZ Kologrivskij Les name after M.G. Sinicin. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD5. 2 records from A new Schistura from the Salween basin in western Yunnan (Teleostei: Nemacheilidae). 101 records from Données de présence collectées sur les odonates. 6188 records from SPC PROCFish/C Fish Observations Solomon Islands 2006. 6444 records from Projet SYRFID 2 (données bibliographiques sur les Syrphes de France). 6 records from Opheliidae (Annelida: Polychaeta) from the western Pacific islands, including five new species. 33 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 23 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 140 records from Status, ecología y conservación de loros Amazona en el Noreste de México. 7740 records from Darling Scarp Survey. 2 records from A new species of Curculionichthys (Siluriformes: Loricariidae) from the north edge of the Brazilian Shield, lower Amazon basin. 6 records from New Neotropical species of Lachesilla Westwood, in species group forcepeta (Psocodea: ‘ Psocoptera’: Lachesillidae). 1454 records from Planktic foraminifera abundance of Hole 26-258A. 4 records from Microplankton abundance at bottle station SEPT-1999-K9. 59 records from Biodiversidad de Herpetos de las Reservas Naturales de la Sociedad Civil del Parque Natural Regional Páramo del Duende, Valle del Cauca, Colombia. 45 records from Phytoplankton abundance at station Rigel_4_2005-04 in April 2005, Chipana, Chile. 5 records from Gamelia bennetti sp. nov., a new Saturniidae species from Trinidad and Tobago (Lepidoptera: Bombycoidea). 3 records from Two new species of Maiestas Distant (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with a new record from Australia. 139 records from Australian Sea Lion and New Zealand Fur Seal Distribution Database from Coastal and Marine Resources Information System (CAMRIS). 370 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-710A. 133 records from Distribution of Uvigerina proboscidea in Late Neogene sediments of DSDP Hole 22-214 in the northern Indian Ocean (Table 1). 9 records from Description of new species of algal-boring Limnoria (Crustacea, Isopoda, Limnoriidae) from Japan and redescription of Limnoria segnoides Menzies, 1957 and L. nagatai Nunomura, 2012. 68 records from The genus Haplodrassus Chamberlin, 1922 in the Mediterranean and the Maghreb in particular (Araneae: Gnaphosidae). 12 records from Five new species of Spartaeus Thorell, 1891 from China (Araneae: Salticidae). 6 records from Provisional checklist of the Tettigonioidea (Insecta: Orthoptera) from São Tomé & Príncipe with taxonomic remarks, bioacoustical data and the description of new taxa. 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 62 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgelände SGD/Viersen. 4 records from Adventive Staphylinidae (Coleoptera) of the Maritime Provinces of Canada: further contributions. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 26 records from Total foraminifera counts from M35/1_MSN1045. 1057 records from Flora genérica de las gramíneas del estado de Tlaxcala. 66 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 557 records from Planktic foraminifera abundance of Hole 49-408. 53 records from Cetacean observations in Avacha Gulf 2005-2009. 322 records from Tetranychus urticae collection records in a predator-prey system: Phytoseiulus persimilis (Acari: Phytoseiidae) and Tetranychus urticae (Acari: Tetranychidae). 1193 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 141 records from (Table 1.2.3.1) Abundance of sympagic meiofauna in the bottom-ice section of Polarstern cruise ANT-XXIII/7 sea-ice cores. 2 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 315 records from Natural History Museum Maastricht (NL) - Herbarium. 1 records from A New Subspecies Of Chrysolina Sanguineocincta (Crotch, 1871) From Turkey (Coleoptera: Chrysomelidae: Chrysomelinae). 399 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 7057 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 482 records from Pez León en Venezuela. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 112 records from Pareronia butterfly specimens at Museum Zoologi Bogor, Indonesia. 1546 records from Données d'odonates récoltées en 2013 et 2014 par le CEN Aquitaine - Suivi Temporel des Libellules (STELI) / PRAO 2013 - 2017. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 31 records from Inventaire des amphibiens en milieux humides sur le site de Fay-sur-Lignon. 116 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/041-2. 434 records from Cetacean distribution around Mayotte Island. 1 records from Amage imajimai sp. nov., a new species of Ampharetidae (Annelida: Polychaeta) from Japanese waters. 749 records from BOEM Sperm Whale Seismic Study (SWSS) PhotoID 2002-2005. 4235 records from NWTRC JP04 Aerial Surveys 2014-2015. 95 records from Total foraminifera counts of trap L2_92_A43. 4 records from Revision of Tynacantha Dallas with description of two new species (Hemiptera: Heteroptera: Pentatomidae: Asopinae). 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 25 records from Notes on Mediterranean Theridiidae (Araneae) – II. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 6990 records from Ethnobotanical surveys species in Benin (West Africa). 425 records from University of Vermont, Pringle Herbarium, North American lichens. 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 3 records from Nannofossil abundance of Hole 1-4. 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 262 records from Nannofossil abundance of Hole 21-205. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 37 records from Berlin - Treptower Park / Karpfenteich. 247577 records from Bacterial diversity and community composition in grassland and forest soils of the German Biodiversity Exploratories. 529 records from El género Bursera en México. Parte II. 13525 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 26 records from Meiofauna en playas de la ciudad de Santa Marta. 443 records from PSUZC-Mammal Collection. 3 records from Two new marine species of Cocconeis (Bacillariophyceae) from the west coast of Sweden. 3 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 371 records from GCP_2017_12_18. 264 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 2 records from Description of a new species of Chrysina Kirby (Coleoptera: Scarabaeidae: Rutelinae) from the Sierra Azul, Oaxaca, Mexico, a new synonymy, and notes on Chrysina species found in the Sierra Azul. 87 records from Gulf of Gdansk. 806 records from Planktic foraminifera abundance of Hole 80-549A. 704 records from NEFSC Aerial Survey - Summer 1998. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 1143 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 6 records from A new forest dwelling button spider from South Africa (Araneae, Theridiidae, Latrodectus). 768 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-101BX. 111 records from Benthic foraminifera abundance of Hole 34-320. 53 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 39099 records from Herbarium Senckenbergianum (FR). 30164 records from Invertebrate Zoology Division, Yale Peabody Museum. 248 records from DREAL Auvergne - Reptiles - 2015. 119 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 916 records from Evaluación de la efectividad de las métricas derivadas de los invertebrados acuáticos para establecer la integridad ecológica de ríos de páramo: caso de estudio del Parque Chingaza. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 330 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V23-82. 1257 records from Sea trout entering the rivers Adour and Nivelle in south-west France at the start of the 21st century. 1 records from The advertisement call of Leptobrachella liui Fei and Ye, 1990 (Anura: Megophryidae). 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 146 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 14 records from Registros de tortuga de río (Podocnemis lewyana) en el marco del Proyecto: Genómica de la conservación para la tortuga de río. 2 records from First record of the cimicomorphan family Plokiophilidae (Hemiptera, Heteroptera) from China, with description of a new species of Plokiophiloides. 45 records from Planktic foraminifera abundance of Hole 73-520. 17 records from Nachtinsekten am Muldenufer. 19 records from Colección de muestras biológicas del Centro Oceanográfico de Canarias. 40 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species. 8 records from Neofidia Strother, a new name for Fidia Baly, 1863 and redescription of Fidia kanaraensis (Jacoby, 1895) with a new host record and notes on natural history (Coleoptera, Chrysomelidae, Eumolpinae). 555 records from NEFSC Aerial Survey - Experimental 2002. 352 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 11093 records from Catálogo de insectos de la colección del Centro de Entomología. 76 records from Records at sea of juveniles southern elephant seals (Mirounga leonina) from Península Valdés, Argentina. 1 records from Emeia gen. nov., a new genus of Luciolinae fireflies from China (Coleoptera: Lampyridae) with an unusual trilobite-like larva, and a redescription of the genus Curtos Motschulsky. 23 records from Catalogue of Coleoptera type specimens housed in the collection of the Museu de Ciências Naturais, Fundação Zoobotânica do Rio Grande do Sul, Brazil. 6 records from Revision of the genus Coeliccia Kirby in Borneo part II: Two new species from the membranipes- group, with a redescription of C. macrostigma Laidlaw (Odonata: Zygoptera: Platycnemididae). 427 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (2), 2008 - Données faune. 2 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 75 records from DAYO: Invasive Alien Reptiles in the Philippines. 3097 records from Synthèse 10x10km de la faune sauvage de la Directive Habitats-Faune-Flore recensée par l'association Vienne Nature de 2013 à 2017. 233 records from New state records for Coniopterygidae (Neuroptera) with an updated list of species in North America north of Mexico. 26 records from Chronicle of Nature - Phenology of Mammals of Kondinskie Lakes National Park named after L. F. Stashkevich. 11 records from Catalogue of Notomastus M. Sars, 1851 (Annelida, Capitellidae) and the description of a new species from the Gulf of California. 2501 records from Aves del Distrito de Páramos en los departamentos de Nariño-Putumayo. 10 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 1247 records from Antarctic Jellyfish. 18 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 75 records from Données naturalistes d'Audrey SAVOURE-SOUBELET. 580123 records from National Trust Species Records. 6756 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 253 records from Pukkellaks i Norge 2017. 20360 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 74 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 80 records from Données naturalistes d'Emmanuel ICARDO. 1822 records from NHM, Heteroptera. 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 7 records from Asian cave-adapted diplurans, with the description of two new genera and four new species (Arthropoda, Hexapoda, Entognatha). 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1182784 records from Australian Museum provider for OZCAM. 5221 records from Acoustic monitoring data of anuran species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 130 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 1 records from 5. Wiener Gemeindebezirk. 39963585 records from Observation.org, Nature data from around the World. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 8 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 7371 records from Mammal records for Dumfries and Galloway. 471 records from Phytoplankton data collected from a diurnal station in Sevastopol Bay (Black Sea) during 1952. 58 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 97 records from Streuobstwiese Stedar 2008. 4054 records from Dados de ocorrência de espécies da flora da Guiné-Bissau. 1549 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 226 records from Fiocruz/CEIOC - Coleção Entomológica do Instituto Oswaldo Cruz. 39471 records from Canadian Museum of Nature Fish Collection. 37971 records from JPB - Herbário Lauro Pires Xavier. 136 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 88 records from A revision of the spider genus Zaitunia (Araneae, Filistatidae). 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 6 records from On four new species of the jumping spider genus Mago O. Pickard-Cambridge, 1882 from South America (Araneae: Salticidae). 4 records from A new species of Uvarus Guignot, 1939 (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) from Florida, USA. 1200 records from 2019_MJIM_IN. 1 records from A new species of Behningia Lestage, 1929 (Ephemerotera: Behningiidae) from China. 2 records from Entomologische Nachrichten und Berichte. 16 records from Revision of Netomocera Bouček (Hymenoptera: Chalcidoidea: Pteromalidae), excluding the Oriental species. 149 records from Données naturalistes de l'inventaire malacologique pour l’élaboration de deux dossiers de création de Réserve naturelle régionale (RNR) - Sites des Terrils n° 11 et 12 du Bois des Dames (Bruay-la-Buissière) et Ex-sablière de Chocques. 907 records from Bats of Poland. 127 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 11 records f
Keywords: GBIF; biodiversity; species occurrences